Where Kindness Is Calculated: Refugee Regimes in South Asia - Sarker, Shuvro Prosun; Bhattacharya, Shreyasi (UI Scholars Hub, 2022)
South Asia, as part of SAARC treaty, comprising of nations such as Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka is not a part of any common system of governance in protecting refugee. These nations have developed their own preference of protection through their practices coupled with mysterious unwillingness to accept international obligations and responsibilities while choosing certain refugee groups to welcome and certain to refuse. Based on this, the article starts with the proposition that this kind of a preferential protection practice that these States have adopted largely, refers to a regime of calculated kindness that labelled refugee status and protection to ambiguity. The article investigates how the major refugee groups have been received in these countries and tries to unearth if there exists a common pattern in the State practices that can characterise a South Asian approach to refugee protection. The article results in establishing the proposition that the ‘kindness’ is calculated based on an ad-hoc measures of refugee protection based around religion, language and culture. Proceeding from this proposition, the article emphasises the need for a uniform refugee protection regime common or unique to all countries in South Asia for regulating refugee movements across South Asia.